2013
DOI: 10.1186/1756-0500-6-104
|View full text |Cite
|
Sign up to set email alerts
|

Sex-differences in reasons for non-participation at recruitment: Geelong Osteoporosis Study

Abstract: BackgroundUnderstanding reasons for non-participation in health studies can help guide recruitment strategies and inform researchers about potential sources of bias in their study sample. Whilst there is a paucity of literature regarding this issue, it remains highly plausible that men and women may have varied reasons for declining an invitation to participate in research. We aimed to investigate sex-differences in the reasons for non-participation at baseline of the Geelong Osteoporosis Study (GOS).MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 19 publications
2
65
0
Order By: Relevance
“…In addition, because 30% of individuals older than 65 years fall every year (Hopewell et al, 2018), and since we specifically searched for individuals who had fallen in the previous year, after our 5 years of inclusion we had likely collected a significant part of the general population. Regarding the small number of men in our sample, it is inherent to the lower number of men than women admitted to the hospital, and who experienced a fall with a low-energy fracture (21% in the initial description of the osteoporosis cohort of the University hospital in Caen (Levasseur et al, 2007) and 16% during the inclusion period of the present study), together with the well-known fact that men are less likely to agree to participate in this type of research (Markanday et al, 2013). Moreover, although our sample size is relatively small, the results of the multivariate logistic regression can be considered as robust because the confidence intervals are relatively narrow except for the MMSE and TMT B-A for which the lower limit confidence interval is, nonetheless, close to two.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, because 30% of individuals older than 65 years fall every year (Hopewell et al, 2018), and since we specifically searched for individuals who had fallen in the previous year, after our 5 years of inclusion we had likely collected a significant part of the general population. Regarding the small number of men in our sample, it is inherent to the lower number of men than women admitted to the hospital, and who experienced a fall with a low-energy fracture (21% in the initial description of the osteoporosis cohort of the University hospital in Caen (Levasseur et al, 2007) and 16% during the inclusion period of the present study), together with the well-known fact that men are less likely to agree to participate in this type of research (Markanday et al, 2013). Moreover, although our sample size is relatively small, the results of the multivariate logistic regression can be considered as robust because the confidence intervals are relatively narrow except for the MMSE and TMT B-A for which the lower limit confidence interval is, nonetheless, close to two.…”
Section: Discussionmentioning
confidence: 98%
“…Women aged 20 years and over were enrolled 1993–1997, with a participation of 77.1%. Details of non‐participation have been described elsewhere . For this study, we included only women aged 50 years and over.…”
Section: Methodsmentioning
confidence: 99%
“…Details of non-participation have been described elsewhere. 28 For this study, we included only women aged 50 years and over. Of the potential 837 women, 87 were excluded because measures of lean mass were unavailable for analysis including 15 with bilateral prostheses.…”
Section: Subjectsmentioning
confidence: 99%
“…We had a 74% response rate to the baseline psychological survey and fewer than expected males and adults responded. Higher research participation rates among females has also been reported from other settings,33 while the higher participation rate among the youth athletes may be explained by parental influence. Nonetheless, there was no difference between responders and non-responders with regard to having sustained a severe injury the previous year.…”
Section: Discussionmentioning
confidence: 61%